EVALUASI KURIKULUM 2013 PADA PEMBELAJARAN AGAMA ISLAM DALAM MENINGKATKAN MORAL PELAJAR (Studi Pada SMP Negeri 24 KabupatenTebo) - Hamirul,; Widya Pratiwi,; Nanang Alhidayat,; Syahwami,; Ariyanto. M,; Nova Elsyra, (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2021)
Implementation of the 2013 Curriculum in the state junior high school 24 Tebo district needs to be evaluated using descriptive methods and qualitative approaches. The data collection technique used in this study was interviewed with 8 informants; Principal of Tebo District 24 Middle School, Deputy Principal for Curriculum Fields; Islamic religion teacher at SMP Negeri 24, Tebo Regency, Chair of the Tebo Regency 24 Middle School Committee; 2 students from Tebo Regency 24 Public Middle School, 2 guardian parents of Tebo Regency 24 Middle School students. The results of the study The implementation of the 2013 curriculum on Islamic Learning in Improving Student Morale in Tebo Regency 24 Public Middle School was carried out to the fullest. This can be seen from the enthusiasm of school principals and teachers in participating in every education and training (training) related to the 2013 curriculum. However, there are still some obstacles in its implementation.